Clinical Spectrum and Treatment Outcomes of Pediatric Hodgkin Lymphoma: A Retrospective Study from a Resource-Limited Setting - Rafique, Nazia; Laique, Muhammad Hassan; Yasmeen, Nuzhat; Zulfiqar, Sughra; Manzoor, Ruqayya; Shaheen, Hijab (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the epidemiological, clinicopathological features, and treatment outcomes of Pediatric Hodgkin Lymphoma (HL) in low- and middle-income countries (LMICs) over 15 years. Study Design: Retrospective Analytical Study Place and Duration of Study: Pediatric Hematology and Oncology Center, Pakistan Institute of Medical Sciences (PIMS) in Islamabad, Pakistan, from Jan 2007 to Dec 2021. Methodology: The study analyzed 155 pediatric HL cases treated at study setting over a period of 15 years retrospectively. Cases were reviewed for age, gender distribution, clinical presentation, histological subtypes, disease staging, treatment response, and survival outcomes. Findings were compared with national and international literature. Results: The mean age at diagnosis was 7.4 years, with 56.1% of cases between 6–10 years and a male-to-female ratio of 4:1. Classical HL (96.1%) was predominant, with mixed cellularity (63.2%) as the most common subtype. Advanced-stage disease (Stage III–IV) was observed in 75% of patients, and B symptoms were present in 63.2%. Despite late presentation, event-free survival (EFS) and overall survival (OS) were 89% and 93.5%, respectively. The relapse rate was 7.1%, with limited salvage success due to a lack of advanced therapeutic modalities. Conclusion: This study highlights significant diagnostic and systemic delays contributing to advanced-stage presentation in pediatric HL. Despite resource limitations, survival outcomes were comparable to international standards, reflecting effective treatment protocols. Measures are needed to work on early detection, referral systems, and oncology infrastructure to further improve paediatric HL outcomes in Pakistan and similar poor countries.